PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, KOMPETENSI PENGGUNA, DAN KINERJA SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS INFORMASI AKUNTANSI - Rika Aprilia Mantika, (2023)
Micro, Small, and Medium Enterprises require high-quality information, one of which is the ability to test out bank products. However, by 2020, only 1% of small and medium-sized businesses were in the bankable sector and eligible for banking system stimulation. This is demonstrated by the fact that many MSME actors continue to use traditional recordkeeping methods, are not technologically literate, and lack information. The purpose of this quantitative study is to investigate the impact of Information Technology Utilization, User Competence, and Accounting Information System Performance on Accounting Information Quality. There are 135 people in the research sample. This study's sample consists of MSME players from the DKI Jakarta. This study's sample consists of MSME actors in the DKI Jakarta area. A questionnaire was used for sampling. SmartPLS with a significance value of 5% was employed in this study's analysis. According to the findings of this study, the use of information technology has no significant effect on the quality of accounting information, however user competence and accounting information system performance have a substantial effect on the quality of accounting information. This research can be used to help MSMEs record their finances using information technology.